Can change of direction speed and reactive agility differentiate female hockey players? - Morland, B.; Bottoms, L.; Sinclair, J.; Bourne, N. (International Journal of Performance Analysis in Sport, 2013)
This study investigated whether pre-planned change of direction speed (CODS) and reactive agility (RA) of teenage female field hockey players could distinguish playing standard and whether they could be used to predict standard of play. Ten female school/club (SCHOOL) standard players (age 16.9 ± 0.7 yrs) and ten female regional performance centre (REGIONAL) standard players (age 17.0 ± 0.7 yrs) underwent a series of sprints involving change of direction through an electronically timed course under three conditions, 1. pre-planned change of direction (PRE); 2. change of direction initiated by reaction to a light source (LIGHT); 3. change of direction initiated by reaction to a hockey specific stimulus (HOCK). Each participant completed four trials in each condition with the best time used for analysis. REGIONAL players completed the HOCK test more quickly than the SCHOOL players (P=0.05), whereas there were no differences between the groups in the other tests. Logistical regression analysis found that none of the tests could be used as a predictor for standard of play. Although a sports specific agility test was performed quicker by REGIONAL players it was not able to predict standard of play and therefore further development is needed for an efficient sports specific test.